THE EFFECT OF IMPLEMENTING COHESIVE TIES BY SAUDI PREP-YEAR PRE INTERMEDIATE STUDENTS ON THEIR WRITTEN TEXTS - Mansour Wahby (European Scientific Journal, ESJ, 2014)
This study aims to measure Saudi prep-year pre-intermediate students’ writing proficiency (represented in writing scores) in relation to their knowledge of implementing cohesive devices in writing a texture. An experiment is conducted with two research tools to test students’ writing proficiency and those students’ capability of implementing cohesive ties. All participants were randomly selected from the preparatory year in the Deanery of Academic Services in Taibah University in Medinah, KSA. A closer examination of the data demonstrated that the more students are aware of cohesive ties and how to be used, the higher their English writing scores are and the closer they are from writing texture rather than texts.